(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Medico-legal cases involving trauma have shown rising trend throughout the world. With increase in number of these cases, maxillo-facial and Ear, Nose and Throat (ENT) injuries have become more important. The aim of the present study is to highlight the pattern and profile of medico-legal cases related to maxillo-facial and ENT injuries presenting to casualty department of Government Medical College and Hospital, Haldwani, Uttarakhand, during the period of one year. In the present study, a total of 385 medico-legal cases related to maxillo-facial and Ear, Nose and Throat (ENT) injuries were included, of which, male predominance was observed in 74.28% cases. Majority (83.12%) cases belonged to Hindu community. Maximum cases reported from the age group of 21–30 years (28.83%) followed by age group of 31–40 years. In majority of cases (76.63%), alleged manner of incidence was accident followed by homicide. Majority of cases (53.5%) were of road traffic accident (RTA), followed by fall from height (20.5%) and physical assault (19.7%). In the present study, commonest bone affected was nasal (58.2%) followed by mandible and nasal bleeding (38.16%) was most common soft tissue injury. These injuries can be reduced by proper education, awareness and training of safety standards as most of them are caused by RTA.